FERVE: between denunciation and institucional representation - Fonseca, Dora (Faculdade de Ciências e Letras - Unesp - Araraquara., 2012)
In this paper we intend to give account of the appearance, evolution, objectives and potentialities of the movement FERVE. The role that it takes in the field of the struggles against precarity is analysed, as well as its functioning and organization in the context of the existence of cyberactivism networks. The relationships of the movement with political organizations and unions will be closely examined with the objective of delineating possible contributions to the field of the representation of the precarious workers, as well as the likeliness of the transformation of its organizational character. The main purpose is to delineate the guidelines for further analysis of the emergent movements of precarious workers.